Increasing access to business incubation services for cottage start-ups to promote inclusive entrepreneurship in Southwest Uganda - Tumuhimbise, Manasseh; Musiita, Benjamin; Katarangi, Asaph Kaburura; Kahangane, Geoffrey; Wanito, Atwine Daniel; Akampwera, Sheila (Journal of Economics and Behavioral Studies, 2024)
In the last 30 years, Uganda has grappled with rising unemployment, notably impacting small businesses, with 85% failing within the first five years. This trend is pronounced in the cottage industry, where 46% of businesses couldn’t sustain operations in 2017. In Mbarara district, 65% of cottages established in 2015 had closed or relocated by 2019. This study explores the impact of business incubation support services on reducing cottage start-up failures and promoting inclusive entrepreneurship in Mbarara City. Examining 800 start-ups in handicrafts, soap making, pottery, tailoring, and shoe making, the study employed a correlational research design. The data, collected through a Likert scale questionnaire, revealed that access to finance, capacity building, and information technology (ICT) adoption accounted for 13.2% of the variation in cottage enterprise growth potential. Notably, increased finance positively correlated with growth, while capacity building showed no significant association. ICT adoption, however, had a negative correlation. The study emphasizes the need for cottage entrepreneurs to receive more training on product improvement, additional capital, equipment, and partnerships. In conclusion, access to capacity building, funding, and ICT adoption is pivotal for cottage enterprise expansion, advocating for incubation support services to enhance collaboration, funding, equipment, and product improvement training for cottage entrepreneurs.